The Role of Chinese Customs in Support of Trade Facilitation for International Business - FENG, MENGJIAO (2013)
With the increased trade activities through imports and exports in China, attention to customs procedures is increasing for the purpose of maintaining control. This paper intends to study the role of Chinese customs to facilitate trade to promote foreign trade and business through various logistics that are involved in these trade activities from within and outside the Chinese boundaries. The research methodology adopted for this paper is exploratory research, in which secondary data has been used to analyze the various dimensions of the research. The research has been built on research work done by various researchers of China, and World Bank, United Nations and OECD.